DEVELOPING THE STUDENT CHARACTER VALUE BASED ON LOCAL WISDOM BY IMPLEMENTING THE PROJECT BASED LEARNING MODEL - Tarita Aprilani Sitinjak; Ni Putu Diah Agustin Permanasuri (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Developing human resources is one of education’s duty, beside increasing the the learning outcome, improving student cahrachter is a must in order to gain a qualified human resource. The research background is to develop student’s character as a mention in Pelajar Pancasila character. The research aim is to improving the student character based in local wisdom character by implementing the Project Based Learning (PjBL) model. Data was colecting by doing observation, interview and documentation. The resut showed an increase in character values in aspects of independent and resposnsible. Brief conclssion of the research is the project-based learning model can improve the character values of students.